Konflik Agraria Antara Masyarakat Dengan Perusahaan Pemegang HPHTI di Kabupaten Pelalawan - Sobri S.IP., MA (UIR PRESS, 2017)
Agrarian conflict between the people living in the villages of the pelalawan district is due to the change of government policy related to the pattern of management of natural resources such as forest, land and river, from